2021
DOI: 10.1007/s00701-021-04829-9
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes secreted from sonic hedgehog-modified bone mesenchymal stem cells facilitate the repair of rat spinal cord injuries

Abstract: Background Spinal cord injuries (SCIs) can cause a loss of neurons and associated sensory and motor functionality below the injured site. No approaches to treating SCIs in humans have been developed to date. Exosomes are extracellular vesicles that hold promise as a potential therapeutic modality when treating such injuries. The present study was thus designed to determine whether sonic hedgehog (Shh)-overexpressing bone mesenchymal stem cell (BMSC)-derived exosomes were protective in the context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Further, the capacity of EVs to transfer biological and pharmaceutical molecules to specific tissues and cell types has raised considerable interest in their development as biocompatible drug delivery systems [reviewed in Sluijter et al (2018) ; Pirisinu et al (2020) ; Herrmann et al (2021) ; and Rankin-Turner et al (2021) ]. At present, https://www.clinicaltrials.gov lists 224 studies which include “exosome,” 84 with “extracellular vesicle,” 9 with “nanocarrier,” 4 with “engineered exosome,” and 2,101 with “liposome.” While a portion of these are diagnostic/biomarker studies, most are clinical trials based on pre-clinical therapeutic success in wound healing (NCT04761562, NCT04281901, and NCT04664738) ( Jia et al, 2021 ; Zhao et al, 2021 ), heart disease (NCT04327635) ( Aday et al, 2021 ; Hu S. et al, 2021 ), COVID-19 (NCT04657458, NCT04493242, NCT04276987, NCT04747574, NCT04389385, and NCT04969172) ( Mitrani et al, 2021 ), infectious disease (NCT01478347, NCT01717638, and NCT04350138), diabetes (NCT02138331), stroke (NCT03384433), arthritis (NCT04223622), and drug delivery (NCT01294072, NCT02889822, and NCT04217096). While classified as EV therapies, such studies are more often comprised of a variety of secreted components (i.e., secretome containing soluble factors and EVs) than purified EVs ( Table 1 ).…”
Section: Current Developments In Ev-based Therapeuticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, the capacity of EVs to transfer biological and pharmaceutical molecules to specific tissues and cell types has raised considerable interest in their development as biocompatible drug delivery systems [reviewed in Sluijter et al (2018) ; Pirisinu et al (2020) ; Herrmann et al (2021) ; and Rankin-Turner et al (2021) ]. At present, https://www.clinicaltrials.gov lists 224 studies which include “exosome,” 84 with “extracellular vesicle,” 9 with “nanocarrier,” 4 with “engineered exosome,” and 2,101 with “liposome.” While a portion of these are diagnostic/biomarker studies, most are clinical trials based on pre-clinical therapeutic success in wound healing (NCT04761562, NCT04281901, and NCT04664738) ( Jia et al, 2021 ; Zhao et al, 2021 ), heart disease (NCT04327635) ( Aday et al, 2021 ; Hu S. et al, 2021 ), COVID-19 (NCT04657458, NCT04493242, NCT04276987, NCT04747574, NCT04389385, and NCT04969172) ( Mitrani et al, 2021 ), infectious disease (NCT01478347, NCT01717638, and NCT04350138), diabetes (NCT02138331), stroke (NCT03384433), arthritis (NCT04223622), and drug delivery (NCT01294072, NCT02889822, and NCT04217096). While classified as EV therapies, such studies are more often comprised of a variety of secreted components (i.e., secretome containing soluble factors and EVs) than purified EVs ( Table 1 ).…”
Section: Current Developments In Ev-based Therapeuticsmentioning
confidence: 99%
“…There are now clinical trials further evaluating the safety and efficacy of this treatment for COVID-19 (NCT04384445, NCT04657406). Another major application of EV therapies is in accelerated and improved healing and regeneration of damaged tissue ( Dalirfardouei et al, 2021 ; Hu S. et al, 2021 ; Jia et al, 2021 ; Lou et al, 2021 ; Saludas et al, 2021 ; Zhao et al, 2021 ). There are promising results in the utilization of EVs to repair arthritic joints (NCT04223622) ( Cosenza et al, 2017 ; Wang et al, 2017 ; Wu et al, 2019 ; Zhang S. et al, 2019 ; Jin et al, 2020 ) and spinal-cord injuries ( Rong et al, 2019 ; Li L. et al, 2020 ; Jia et al, 2021 ), with tissue restoration in EV treatments exceeding that of untreated animals/tissue.…”
Section: Current Developments In Ev-based Therapeuticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, activated Shh signaling pathway was found to promote recovery from SCI in a rat model [ 17 ]. Our prior study found that Shh-overexpressing BMSC-derived exosomes can facilitate SCI repair in rats [ 18 ]. However, whether Shh is necessary for BMSC-derived exosomes to augment SCI repair is yet to be studied.…”
Section: Introductionmentioning
confidence: 99%